Monomeric C-Reactive Protein in Serum With Markedly Elevated CRP Levels Shares Common Calcium-Dependent Ligand Binding Properties With an in vitro Dissociated Form of C-Reactive Protein - Williams, Robert D.; Moran, Jennifer A.; Fryer, Anthony A.; Littlejohn, Jamie R.; Williams, Harry M.; Greenhough, Trevor J.; Shrive, Annette K. (Frontiers in Immunology, 2020)
A monomeric form of C-reactive protein (CRP) which precipitates with cell wall pneumococcal C polysaccharide (CWPS) and retains the ability to reversibly bind to its ligand phosphocholine has been produced through urea-induced dissociation at an optimised concentration of 3 M urea over a 10-week period. Dissociated samples were purified via size exclusion chromatography and characterized by western blot, phosphocholine affinity chromatography and CWPS precipitation. Human serum samples from patients with raised CRP levels (>100 mg/L as determined by the clinical laboratory assay) were purified by affinity and size exclusion chromatography and analysed (n=40) to determine whether circulating monomeric CRP could be detected ex vivo. All 40 samples tested positive for pentameric CRP via western blot and enzyme linked immunosorbent assay (ELISA) analysis. Monomeric C-reactive protein was also identified in all 40 patient samples tested, with an average level recorded of 1.03 mg/L (SE=+/-0.11). Both the in vitro monomeric C-reactive protein and the human serum monomeric protein displayed a molecular weight of approximately 23kDa, both were recognised by the same anti-CRP monoclonal antibody and both reversibly bound to phosphocholine in a calcium-dependent manner. In common with native pentameric CRP, the in vitro mCRP precipitated with CWPS. These overlapping characteristics suggest that a physiologically relevant, near-native monomeric CRP, which retains the structure and binding properties of native CRP subunits, has been produced through in vitro dissociation of pentameric CRP and also isolated from serum with markedly elevated CRP levels. This provides a clear route towards the in-depth study of the structure and function of physiological monomeric CRP.